Analysis and Design Recommendation of Corrugated Steel Plate Shear Wall with Modification of Wall Opening and Reduced Beam Section - Rambak, Ezra Pasereng; Suswanto, Budi; Sugihardjo, Hidajat (Jurnal Aplikasi Teknik Sipil, 2021)
Corrugated Steel Plate Shear Wall (CSSW) is one type of seismic-resistant steel structure stiffener that can anticipate large amounts of earthquake energy. There is difficulty in informing the behavior of the nonlinear corrugated steel plate shear wall behavior, in particular the wall with an opening. Because the CSSW design methodology has not been included in the design standards. In this paper, research has been carried out on new methods that can be used in CSSW. This research was carried out by applying loading to the specimen with two models, namely Vertical CSSW and Horizontal CSSW with an opening of 10%. From the results of this study, the highest ductility value was 16.0 and had an average energy dissipation value of 7862.63 kN.m. The results of this study indicate that each of the Vertical and Horizontal CSSW specimens was able to increase the stiffness and capacity of the structure.